Explaining the Challenges Facing the Development of Entrepreneurial University: The Application of Grounded Theory - HEYDARIAN, NEDA; NAJAFABADI, MARYAM OMIDI; LASHGARARA, FARHAD; MIRDAMADI, MEHDI (The journal of contemporary issues in business and government, 2021)
An entrepreneurial university is a new approach to improving the quality of higher education systems around the world. However, the lack of a transparent mechanism has prevented Iranian universities from turning into an entrepreneurial university. In this regard, the present study aimed to identify the barriers facing the development of an entrepreneurial university in Islamic Azad University (Science and Research Branch). The statistical population was composed of managers and faculty members of the university, of whom 24 respondents were selected by the snowball sampling method. Using Grounded Theory, the respondents were subjected to in-depth interviews. Data were analyzed by NVivo10 software. In total, 55 codes were extracted in the open-coding step. Finally, eight main concepts were derived through the codifying hierarchy of Grounded Theory according to which the challenges included academic, distance, operational, human, management, strategic, political, and cultural ones. Each concept expresses one aspect of the subject. According to the results, the distance challenge is the most important challenge of the entrepreneurial university development at Islamic Azad University. The paper is concluded with some practical suggestions to facilitate the path to an entrepreneurial university.